2011
DOI: 10.1590/s1982-56762011000600003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of UV-C irradiation on Guignardia citricarpa and on postharvest control of citrus black spot

Abstract: Black spot, caused by Guignardia citricarpa, is one of the main diseases affecting citrus fruits. UV-C irradiation is known to have potential to be used as an alternative method to supplement or replace the use of fungicides, especially because it promotes resistance against pathogens. The aim of this work was to evaluate the in vitro effects of UV-C irradiation on G. citricarpa development and on the control of black spot in postharvest orange. Additionally, changes in skin color of the fruit as a result of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Until the extent of our knowledge, this result is the first achieved in preharvest condition for controlling powdery mildew on tomato plants after natural infection by the fungus. Reports of UV-C effect in agriculture, are mainly related with postharvest diseases management [8, [47][48][49][50]; and the use of UV-C for controlling diseases in preharvest condition has been poorly achieved, particularly on powdery mildew diseases. Van Hemelrijck et al [25], showed that UV-C, on apples and strawberries with powdery mildew, significantly reduced the disease without negative effects on plant performance in field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Until the extent of our knowledge, this result is the first achieved in preharvest condition for controlling powdery mildew on tomato plants after natural infection by the fungus. Reports of UV-C effect in agriculture, are mainly related with postharvest diseases management [8, [47][48][49][50]; and the use of UV-C for controlling diseases in preharvest condition has been poorly achieved, particularly on powdery mildew diseases. Van Hemelrijck et al [25], showed that UV-C, on apples and strawberries with powdery mildew, significantly reduced the disease without negative effects on plant performance in field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…where UVC at doses of 7.28 and 15.66 kJ m −2 were able to control the incidence of citrus black spot disease that was naturally infected on fruits during storage period (Canale et al, 2011). Nigro, Ippolito, Lattanzio, Venere, and Salerno (2000) reported that UVC at doses of 0.50 and 1.00 kJ m −2 significantly reduced the natural infection of Botrytis storage rot on strawberry fruits.…”
Section: Effect Of Uvc Irradiation In Reducing Crown Rot Disease Onmentioning
confidence: 99%
“…UVC is able to enhance the storability of fresh produces by triggering natural disease resistances (Chang‐hong, Lu‐yun, Xian‐ying, Xiao‐xu, & Tie‐jin, ). Several findings revealed the ability of UVC radiation in reducing deterioration of fruits and vegetables when applied after harvest, for instance, in the case of oranges (Canale, Benato, Cia, Haddad, & Pascholati, ; Gunduz, Juneja, & Pazir, ), peppers (Rodoni, Zaro, Hasperue, Concellon, & Vicente, ), “Tatsoi” baby leaves (Tomas‐Callejas, Oton, Artes, & Artes‐Hernandez, ), and button mushrooms (Guan, Fan, & Yan, ).…”
Section: Introductionmentioning
confidence: 99%
“…A ausência de controle da antracnose e das podridões pedunculares em abacate pode ser atribuída ao fato da radiação UV-C não penetrar no tecido dos frutos e, portanto, não atingir as infecções já estabelecidas (LU et al, 1993) e não ter ocorrido indução de resistência. Em contraste a estes resultados, outros autores relataram eficiência da radiação UV-C no controle de doenças quiescentes em maçã (STEVENS et al, 2005, BARTNICKI et al;), manga (TERAO et al, 2015 e citros (CANALE et al, 2011).…”
Section: Resultsunclassified